Mechanisms of lymphoma clearance induced by high-dose alkylating agents - Lossos, Chen (Cancer Discov, 2019)
The extraordinary activity of high-dose cyclophosphamide against some high-grade lymphomas was described nearly 60 years ago. Here we address mechanisms that mediate cyclophosphamide activity in bona fide human double-hit lymphoma. We show that antibody resistance within the bone marrow (BM) is not present upon early engraftment but develops during lymphoma progression. This resistance required a high tumor: macrophage ratio, was recapitulated in spleen by partial macrophage depletion and was overcome by multiple, high-dose alkylating agents. Cyclophosphamide induced ER-stress in BM-resident lymphoma cells in vivo that resulted in ATF4-mediated paracrine secretion of VEGF-A, massive macrophage infiltration and clearance of alemtuzumab-opsonized cells. BM macrophages isolated after cyclophosphamide treatment had increased phagocytic capacity that was reversed by VEGF-A blockade or SYK inhibition. Single-cell RNA sequencing of these macrophages identified a “super-phagocytic” subset that expressed CD36/FcgRIV. Together, these findings define a novel mechanism through which high-dose alkylating agents promote macrophage-dependent lymphoma clearance.